Kritika : essays on intellectual property. - Ghidini, Gustavo; Ullrich, Hans; Drahos, Peter (Kritika: essays on intellectual property ;, 2021)
"The fields of intellectual property have broadened and deepened in so many ways that commentators struggle to keep up with the ceaseless rush of developments and hot topics. Kritika: Essays on Intellectual Property is a series that is designed to help authors escape this rush. It creates a forum for authors who wish to more deeply question, investigate and reflect upon the evolving themes and principles of the discipline. The essays in this 5th volume in the series come from authors who, after a lifelong engagement with various fields of intellectual property (including its socio-economic foundations), reflect on the events and processes that, in their scholarly experience, most significantly impacted on the great evolutionary trends in their particular fields. These reflections span a wide arc from the contradictory history of the regulation of employee inventions and works, to the status of intellectual property as market regulation under public international law; from the trajectories of trade mark protection in the European Union, to the paradigmatic changes copyright law has undergone as a result of technological change; from the influence of the human rights movement on perceptions of intellectual property, to the pendulum swings of patent protection in gene technology inventions; and finally, from the impact of the TRIPS Agreement and bilateral TRIPS plus agreements on IP in the pharmaceutical sector, to the continuing development of copyright for works of art and of the resale right in the PR China. With contributions from: Niklas Bruun, Thomas Cottier, Annette Kur, Hector L. MacQueen, Sam Ricketson, Dianne Nicol, Jayashree Watal, Zhou Lin"--